Innovations in rural and agricultural finance: Rural banking: The case of rural and community banks in Ghana - Nair, Ajai; Fissha, Azeb (International Food Policy Research Institute, 2010)
Before the late 1970s, rural dwellers in Ghana had almost no access to institutional credit for farm and nonfarm activities, and in many rural communities, secure, safe, and convenient savings and payment facilities hardly existed. In response to this situation, the Government of Ghana took several measures to increase access to credit in rural areas, including facilitating the establishment of rural and community banks (RCBs). This brief discusses the history of RCBs, their business model, their services, and their financial performance. It then draws some lessons relevant for others involved in or planning similar initiatives.